1999
DOI: 10.1046/j.1365-2826.1999.00353.x
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Growth Hormone Secretagogues and Neuropeptide Y on Hypothalamic Hormone Release from Acute Rat Hypothalamic Explants

Abstract: Growth hormone (GH) secretagogues (GH-releasing peptides and their non-peptide analogues) stimulate growth hormone release via specific G-protein coupled receptors both directly from the pituitary gland and through stimulation of the hypothalamus. The exact mechanism of action in the hypothalamus is not known. The presence of endogenous GH releasing hormone (GHRH) seems to be necessary for the in-vivo actions of growth hormone secretagogues (GHSs), but data suggest that further factors must be involved as well… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
56
0
1

Year Published

2003
2003
2013
2013

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(59 citation statements)
references
References 67 publications
(95 reference statements)
2
56
0
1
Order By: Relevance
“…There are data to A c c e p t e d M a n u s c r i p t 19 suggest that ghrelin stimulates the HPA axis at a hypothalamic level, at least in part via arginine vasopressin (AVP) and CRH (Coiro et al, 2005;Korbonits et al, 1999a;Mozid et al, 2003). It has been shown that NPY can stimulate CRH and AVP release from the rat hypothalamus (Korbonits et al, 1999b), therefore the effect of ghrelin on CRH and AVP could occur through direct action on CRH and AVP neurons in the paraventricular nucleus, or may occur indirectly via NPY (Mozid et al, 2003). Ghrelin does not have direct stimulatory effects on adrenal hormone secretion (Andreis et al, 2003;Barreiro et al, 2002).…”
Section: Ghrelin and Hypothalamic-pituitary-adrenal Axismentioning
confidence: 99%
“…There are data to A c c e p t e d M a n u s c r i p t 19 suggest that ghrelin stimulates the HPA axis at a hypothalamic level, at least in part via arginine vasopressin (AVP) and CRH (Coiro et al, 2005;Korbonits et al, 1999a;Mozid et al, 2003). It has been shown that NPY can stimulate CRH and AVP release from the rat hypothalamus (Korbonits et al, 1999b), therefore the effect of ghrelin on CRH and AVP could occur through direct action on CRH and AVP neurons in the paraventricular nucleus, or may occur indirectly via NPY (Mozid et al, 2003). Ghrelin does not have direct stimulatory effects on adrenal hormone secretion (Andreis et al, 2003;Barreiro et al, 2002).…”
Section: Ghrelin and Hypothalamic-pituitary-adrenal Axismentioning
confidence: 99%
“…In addition, NPY may suppress the somatotrophic axis via stimulation of hypothalamic somatostatin release. 44,45 Hence, the observed reduction in PeVN somatostatin mRNA expression in obese A y /a mice may be secondary to reduced Arc NPY mRNA expression. Since NPY inhibits the growth axis, 20,21 a reduction in Arc NPY would increase circulating GH and hence IGFI levels.…”
Section: Discussionmentioning
confidence: 98%
“…In contrast to the fasted human, the fasted male rat shows dramatically reduced pulsatile GH release (Tannenbaum et al 1979, Bruno et al 1990, Janowski et al 1993. The fasting-induced fall in GH is thought to be due to a decrease in hypothalamic GHRH expression (Bruno et al 1990, Ghigo et al 1997, Vuagnat et al 1998, Carro et al 1999) brought about by the inhibitory actions of neuropeptide Y (NPY) (Minami et al 1998, Korbonits et al 1999. However, consistent with the fasted human, food deprivation in the rat leads to peripheral GH resistance and reduced IGF-I (Bornfeldt et al 1989), and increased pituitary sensitivity to GHRH (Sugihara et al 1996).…”
Section: Introductionmentioning
confidence: 99%